2017
DOI: 10.5937/specedreh16-14408
|View full text |Cite
|
Sign up to set email alerts
|

Lexical diversity in narrative discourse of children with specific language impairment

Abstract: Rezultati su pokazali da deca sa SJP imaju značano slabija postignuća u pogledu leksičke raznovrsnosti u poređenju sa decom tipičnog razvoja (p≤0,00). Takođe, deca sa SJP su imala značajno 1 Rad je proistekao iz projekta ,,Evaluacija tretmana stečenih poremećaja govora i jezika", ON 179068 (2011ON 179068 ( -2017, čiju realizaciju finansira Ministarstvo prosvete, nauke i tehnološkog razvoja Republike Srbije.2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The results of this study showed that this subtype of DLD children have significantly worse performance in the domain of lexical processing and diversity. Additionally, DLD risk children progressed more slowly within all observed lexical abilities, including naming objects and activities 20 .…”
Section: Ph and Language Developmentmentioning
confidence: 95%
See 4 more Smart Citations
“…The results of this study showed that this subtype of DLD children have significantly worse performance in the domain of lexical processing and diversity. Additionally, DLD risk children progressed more slowly within all observed lexical abilities, including naming objects and activities 20 .…”
Section: Ph and Language Developmentmentioning
confidence: 95%
“…In addition to the above, DLD children also have significant difficulties in using words in spontaneous speech. Namely, studies of lexical diversity (LD) in speech samples of DLD children showed that these children use significantly less of all types of words 13,14 and significantly less content words (nouns, verbs, adjectives) 13,15 , comparing to TD peers.…”
Section: Developmental Language Disordermentioning
confidence: 99%
See 3 more Smart Citations